Evaluation of mesoporous CrB particles synthesized via sol-gel method as potential antibacterial interior paint nano-additive - Filiz, Bilge Coskuner; Elalmis, Yeliz Basaran; Yapaoz, Melda Altikatoglu; Figen, Aysel Kanturk (SPRINGER, 2025)
Antibacterial particles are increasingly explored as additives to improve the health and safety properties of interior paints. This report introduces evaluation of CrB particles as an potential antibacterial additive into paints. The CrB particles were synthesized by sol-gel method in presence of chrome salt, citric acid as alkoxide agent and boric acid precursor followed by nitrate combustion process. The effect of elemental ratio (Cr:B = 1:3 and 3:1) and calcination process (250-550 degrees C) on the antibacterial activity of the particles were investigated against gram negative Escherichia coli (E. coli, ATCC 25922) and gram positive Staphylococcus aureus (S. aureus, ATCC 25923). Statistical analysis of antibacterial activity results and synthesis parameters via interaction plots and ANOVA analysis indicated that lower Cr:B ratio (Cr:B = 1:3) and higher calcination temperature (550 degrees C) resulted in improved particle activity over both gram negative and positive bacteria growth. The amorphous Cr1B3@550 codded particles with structural characteristics of 47 m2/g surface area, 12 nm pore size and 150 mu m accumulated particles with 50 nm size were used as antibacterial additives for wall paint, which improved antibacterial activity performance by %75 for S. aureus and %63 for E. coli. Sol-gel synthesized Cr-B particles tested as antibacterial additive for interior paint.Tests performed against (, ATCC 25922) and (, ATCC 25923).Interaction plots and ANOVA analyses showed activity and synthesis parameters have direct relationship.Cr-B particles showed great potential for antibacterial interior paints, healthcare products or construction materials.
Keywords: Sol-gel synthesis; Escherichia coli; Staphylococcus aureus; Antibacterial; Nano-additive; Mesoporous particles; Functional material; ANTIMICROBIAL ACTIVITY; CALCINATION TEMPERATURE; OPTICAL-PROPERTIES; NANOPARTICLES; CHROMIUM; NIO; BORON; Materials Science